Risk Factors for Development of Diabetes Insipidus and Syndrome of Inappropriate Antidiuretic Hormone Secretion after Transsphenoidal Resection of Pituitary Adenoma - Petito, Gabrielle; Hu, Alex; Zhang, Grace; Min, Susie; Tripathi, Siddhant H.; Kumar, Adithya; Shukla, Geet; Shah, Sanjit; Phillips, Katie M.; Jana, Suman; Forbes, Jonathan A.; Zuccarello, Mario; Andaluz, Norberto O.; Sedaghat, Ahmad R. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Background We aimed to determine the incidence and risk factors for development of diabetes insipidus (DI) and syndrome of inappropriate antidiuretic hormone secretion (SIADH) after transsphenoidal hypophysectomy (TSH) for resection of a pituitary adenoma.Methods This was a retrospective study of 403 adult patients undergoing TSH for pituitary adenoma. Clinical variables, tumor characteristics, and operative factors were collected. Incidences of DI and SIADH were determined, including timing in the perioperative period. Independent predictors of developing DI and SIADH were identified using multivariable logistic regression.Results Following TSH, 21.3% of patients developed DI at a mean 2.6 days and 7.4% developed SIADH at a mean 4.7 days. DI was negatively associated with older age (odds ratio [OR] = 0.98, 95% confidence interval [CI]: 0.96–0.99, p = 0.029). DI was positively associated with female sex (OR = 2.26, 95% CI: 1.24–4.11, p = 0.008), increase in anteroposterior tumor size (OR = 1.54, 95% CI: 1.11–2.13, p = 0.010), intraoperative cerebrospinal fluid (CSF) leak (OR = 2.29, 95% CI: 1.25–4.19, p = 0.008), and every 100 mL of estimated blood loss (EBL) (OR = 1.18, 95% CI: 1.01–1.39, p = 0.046). Development of SIADH was positively associated with intraoperative CSF leak (OR = 3.56, 95% CI: 1.24–10.21, p = 0.018) on multivariate analysis.Conclusion DI and SIADH occur in the minority of patients undergoing TSH, but vigilance for their development must be maintained for days after the surgery. Development of DI after TSH is multifactorial, having possible patient-specific risk factors and risk related to the complexity of surgical dissection, reflected by tumor size, intraoperative CSF leak, and EBL. Development of SIADH could be associated with intraoperative CSF leak occurrence.
Keywords: SIADH; diabetes insipidus; pituitary; transsphenoidal; endoscopic; risk; incidence